THERAPEUTIC ANGIOGENESIS BY GROWTH FACTORS AND BONE MARROW MONONUCLEAR CELLS ADMINISTRATION: BIOLOGICAL FOUNDATION AND CLINICAL PROSPECTS - D. V. Bulgin; O. V. Andreeva (Вестник трансплантологии и искусственных органов)
Angiogenesis is the process of new capillary formation by migration and proliferation of differentiated endothelial cells from pre-existing microvascular network. A number of angiogenic molecules and cell populations are involved in this complex of new vessel formation cascades resulting in the determination and organization of new tridimensional vascular network. The goal of therapeutic angiogenesis is to stimulate angiogenesis to improve perfusion, to deliver survival factors to sites of tissue repair, to mobilize regenerative stem cell populations, andultimately to restore form and function to the tissue. Growth factors and bone marrow as a source of bone marrow mononuclear cells represent a very interesting research fi eld for the realization of therapeutic angiogenesis in ischemic tissues. They provide a potential key component in the healing processes of ischemic injured tissues.